Teaching reading comprehension by using 3H (here, hidden, head) strategy - Cut Sarah Maqfirah (Universitas Syiah Kuala, 2017)
The purpose of this research was to find out the effectiveness of using the 3H strategy (Here, Hidden, and in my Head) for teaching reading comprehension to second grade students at Inshafuddin Boarding Middle School, Banda Aceh and also to find out the students’ responses to learning reading using the 3H strategy. This study used an experimental research design. The sample was selected by purposive sampling; the writer chose class VIII A as the experimental group (EG) and class VIII C as the control group (CG). The instruments used for collecting the data were a pre-test and a post-test plus a questionnaire. The results showed that the use of the 3H strategy was effective for teaching reading comprehension. Moreover, the results from the questionnaire showed that the majority of the students gave positive responses toward the use of the 3H strategy.